Perubahan Pola Hubungan Masyarakat-Pemerintah: Refleksi Atas Penanganan Aduan Publik Melalui Media Sosial di Kota Makassar - Aina, Asri Nur (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
This research explores the dynamics of interaction between the public and the government through social media, with a focus on government activities towards public complaints in Makassar City. Through qualitative methods, data was collected from identity-verified public complaints and explored through in-depth interviews with informants from the agencies that are the object of complaints. The results of the study highlighted the important role of social media in monitoring government performance, increasing public participation in public service oversight, and shaping public opinion space as a check and balance mechanism. The findings show that the use of social media has had a positive impact in improving the government's response to public complaints regardless of social status, although social stratification still plays a minor role in some cases. The use of social media also facilitates responsive and accurate public services, especially in terms of the speed of response and the level of accuracy of government responses. However, challenges remain related to complaint handling, which requires substantial planning and budgeting as well as coordination across authorities. This study illustrates the importance of social media integration in local government practices to improve transparency, accountability and responsiveness in public services, especially in the context of Makassar City, which has declared itself a metaverse city.